STAT1 gain-of-function in 12 Moroccan patients: Clinical and genetic insights - Bouchra Baghad; Ibtihal Benhsaien; Fatima-zahra El Fatoiki; Hind Ouair; Abderrahmane Moundir; Abderrahmane Errami; Maha Soussi-Abdellaoui; Mélanie Migaud; Jean-Laurent Casanova; Anne Puel; Jalila El Bakkouri; Ahmed Aziz Bousfiha; et al. (Journal of Human Immunity, 2026)
Heterozygous gain-of-function (GOF) variants in STAT1 are the most frequent genetic cause of chronic mucocutaneous candidiasis (CMC). Data from Africa remain scarce. We conducted a cross-sectional study at Ibn Rochd University Hospital, Casablanca (2016–2021), enrolling patients with persistent or recurrent mucocutaneous and/or invasive fungal disease. Whole-exome and/or Sanger sequencing were performed, with pathogenicity assessed using ACMG/AMP criteria. We identified 12 patients from 11 kindreds carrying 10 distinct heterozygous STAT1 GOF variants. CMC was the dominant manifestation (11/12, 91%). Mycobacterial infections were documented in 42% of patients and bacterial infections in 50%; one patient presented with cryptococcal meningitis. Autoimmunity was observed in three patients. Two patients died. The c.194A>G (p.D65G) variant, found in a father–son pair, may represent the first clinical description of this substitution as a STAT1 GOF variant. This first dedicated Moroccan cohort demonstrates substantial allelic heterogeneity and a clinical phenotype dominated by infections, particularly tuberculosis, with less frequent autoimmune manifestations than in Western cohorts.